(untitled) (Research, Society and Development, 2021)
The absence of remaining bone tissue from the alveolar ridge has been a major problem for aesthetic and functional rehabilitation in patients. The autogenous bone graft is the ideal material for reconstruction of the maxillary and mandibular borders. The choice of donor area, whether intraoral or extraoral, is related to the quantity and quality of the bone graft required for each case. The present study aims to report a case clinical study of maxillary reconstruction in a patient after orthognathic surgery using the donor area, the mandibular branch region, and to review the main characteristics related to the surgical technique.